Mixed venous oxygen saturation and clinical significance [Miks Venöz Oksijen Saturasyonu ve Klinik Önemi] - (:unkn) unknown (Anestezi Dergisi, 2015)
Mixed venous oxygen saturation known as global index of tissue oxygenation, is an integral part of hemodynamic monitoring for especially follow-up of critically-ill patients. Although it is needed to insert a pulmonary artery catheter to measure mixed venous oxygen saturation, and it is a major obstacle for the common usage of this hemodynamic parameter, currently it is used by multiple health care centres because of its ability to interfere instantly with the measured tissue oxygenation levels of unstable patients in operation room or intensive care units. In this review, it is aimed to have an updated look at the clinical significance of mixed venous oxygen saturation.
Keywords: Central venous oxygen saturation(ScvO2); Lactate; Mixed venous oxygen saturation(SvO2); Pulmonary artery catheter; Sepsis